Association between relative fat mass and colorectal cancer: a cross-sectional study - Wang, Yaping; Song, Shilong; Zhang, Lu; Zhang, Jingjing (Frontiers in Nutrition, 2025)
AimsWe aimed to investigate the potential association between relative fat mass (RFM) and colorectal cancer (CRC).Design and methodsData from the National Health and Nutrition Examination Survey (NHANES) spanning 1999 to 2020 were analyzed. Associations between RFM and CRC were analyzed using multiple logistic regression. Smoothed curve fitting was performed to conduct the association by sex. The stability of associations was assessed using subgroup analyses and interaction tests.ResultsOverall, 52,281 participants over the age of 20 years were enrolled. The fully adjusted model observed a positive association between RFM and CRC, with one-unit increases in RFM linked to a 3% greater prevalence of CRC (OR = 1.03, 95%CI: 1.01, 1.06). A linear positive association was identified between RFM and CRC in male subjects, while a non-linear relationship was observed in females, with an inflection point at 42. Subgroup analysis revealed that age significantly modified the relationship between RFM and CRC (P for interaction = 0.0085).ConclusionRFM is strongly associated with CRC prevalence in US adults. Further large-scale prospective investigations are warranted to for verification.